Arrivals, Arrivees: Literary Encounters with Berlin in the Weimar and Berlin Republics - Erhard Schütz (Studies in 20th & 21st Century Literature, 2004)
The Neurotic City Attention is the hard currency of media society. Attention is a scarce resource (compare Franck, Crary, and Assmann)...
Keywords: Arrivals; Arrivees; Berlin; Weimar; Republic; Neurotic City; media society; Franck; Crary; and Assmann